Expression of a unique M. tuberculosis DNA MTase Rv1509 in M. smegmatis alters the gene expression pattern and enhances virulence - Manjunath, P.; Ahmad, Javeed; Samal, Jasmine; Rani, Anshu; Sheikh, Javaid Ahmad; Zarin, Sheeba; Ahuja, Yashika; Alam, Anwar; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis (M. tb) genome encompasses 4173 genes, about a quarter of which remain uncharacterized and hypothetical. Considering the current limitations associated with the diagnosis and treatment of tuberculosis, it is imperative to comprehend the disease pathomechanism, and host-pathogen interactions and for identifying new drug targets for intervention strategies. Using in-silico comparative genome analysis, we identified one of the M. tb genes Rv1509 as a signature protein exclusively present in M. tb. To explore the role of Rv1509, a likely methyl transferase, we constructed a knock-in Mycobacterium smegmatis (M. smegmatis) constitutively expressing Rv1509 (Ms_Rv1509). The Ms_Rv1509 led to differential expression of many transcriptional regulator genes as assessed by RNA-seq analysis. Further, in-vitro and invivo studies demonstrated an enhanced survival of Ms_Rv1509 inside the host macrophages.Ms_Rv1509 also promoted phagolysosomal escape inside macrophages, to boost bacterial replication and dissemination. In-vivo infection studies revealed that Ms_Rv1509 survives better than BCG and causes pathological manifestations in the pancreas after intraperitoneal infection.Long-time survival of Ms_Rv1509 resulted in lymphocyte migration, increased T regulatory cells, giant cell formation, and likely granuloma formation in the pancreas, pointing towards the role of Rv1509 in M. tb pathogenesis.